External force estimation of fracture reduction robot based on force residual method. (13th January 2020) - Lei, Jingtao; Zheng, Gongliang; Hu, Lei; Zhang, Lihai; Wang, Tianmiao
Robot-assisted fracture reduction surgery should be highly safe and accurate. It is necessary to accurately determine and control the reduction force of the reduction robot. In this article, a fracture reduction robot is designed with the configuration of the 6-universal-prismatic-universal (6-UPU). The vector method is used to analyze the kinematics of the reduction robot. The Jacobian matrix of the reduction robot and the second-order influence coefficient matrix of the acceleration are obtained. The Lagrangian method is adopted to analyze the dynamic of the reduction robot. The muscle contraction force of the femoral shaft fracture is analyzed based on the Hill model to determine the fracture reduction force. According to changing of the reduction force during the fracture reduction operation, a kind of external force estimation method based on force residual analysis is proposed. When there is no external force sensor at the end of the reduction robot, this method can be used to detect the reduction force in real time. According to the displacement, velocity, and output torque of each branch chain, the reduction force during the reduction operation of the reduction robot can be estimated. A simulation system is conducted and the simulation results show that the fracture reduction force can be estimated and accurately tracked in real time, which is of great significance for the safe operation of the fracture reduction robot.